THE EFFECT OF DOMINANT RISK MANAGEMENT COMPONENTS IN ASSET-LIABILITY MANAGEMENT ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN INDONESIA - Nindyan Permata Sari; Lidya Septiani Silaban; Farah Margaretha Leon (Program Studi Akuntansi Institut Teknologi dan Bisnis Asia Malang, 2026)
This study aims to investigate the effect of bank size, leverage, capital adequacy ratio, interest rate risk, liquidity risk, and credit risk on financial performance. This study focuses on banks listed on the Indonesia Stock Exchange and analyzes financial statements from 2020 to 2024. Purposive sampling was used to select 38 banks for this study. Eviews 9.0 was used for panel data regression analysis. The results show that bank size, capital adequacy ratio, and liquidity risk have a significant positive effect, while credit risk has a significant negative impact. Interest rates and leverage have no effect. This implies that to maintain their financial success in the face of changing economic conditions, banks need to implement efficient risk management.